Behavior of Foamed Concrete under Quasi State Indentation Test: Indenter Size Effects - Affindy, Mohd Zairul; Ahmad Zaidi, Ahmad Mujahid; Abdul Rahman, Ismail (International Journal of Sustainable Construction Engineering and Technology, 2011)
Quasi static indentation test is a method consist of applying a compressive axial load using head of indenter to moulded cylinders at a rate which is within a prescribe range until failure occurs. The behaviour of foamed concrete under indentation test should behave like cellular material behavior. The Stress-strain behavior can be divided into three regimes, elastic regime, plateau regime and densification regime. There is still less research conducted toward foamed concrete under indentation test. It is stated that the standard method to obtain the compressive strength of foamed concrete based on ASTM C39 standard or BS 1881: Part 116:1983 is not captured the true compressive strength of foamed concrete. The compressive strength typically achieved low compressive strength and not behaves like a cellular material behavior. This result is due brittle collapse of the sample. Previous study has shows the compressive strength under indentation test is higher and created a localized deformation. Besides, there is a densified zone created below the indenter region which is end with hemi-spherical shape. . Tear line occur because of exrended in front of the indenter and perpendicular to the indenter surface. This study aims to investigate further about the behavior of foamed concrete. This study was look about effect of densities and size of indenter on behavior of foamed concrete under indentation test. The density used is low density, medium density and high density. Size of indenter used is 20mm, 30mm, 50mm and 70.5mm. Under indentation test, the higher densities, the higher compressive strength and the bigger size of indenter used, the strength is decreased due to the early crack initiation and propagation. It is important to know the ratio used to make sure indentation test is captured the true strength.